Renal Hydatid Cyst in a Child Managed with Albendazole - Pandey, Udesh; Timilsina, Bhusan Raj; Acharya, Samrachana; Paudel, Ujjawal; KC, Sudeep Raj; Pradhan, Sulav (Journal of Nepal Health Research Council, 2023)
Primary Renal hydatid cyst is a rare entity. We report a case of isolated right renal hydatid cyst in a 13-year-old female who presented with pain in the right lumbar region for 4-5 months and a palpable mass in the right upper quadrant. The radiological features were suggestive of a hydatid cyst in the right kidney with no cyst in the liver, lungs, or left kidney. She was managed medically with oral Albendazole tablets (400 mg twice daily). A total of 6 cycles of Albendazole were given with each cycle lasting for 4 weeks and a drug-free period of 2 weeks in between two consecutive cycles and kept on follow-up for a year. Her condition improved with no recurrence on follow-up after one year. Keywords: Albendazole; echinococcus granulosus; renal hydatid cyst.